Optimization of Employee Performance Management: A Study in Human Resources of Atour Hotel in China - Zhao Chunying; Ni Made Ary Widiastini; Fridayana Yudiaatmaja (LP2M IAIN Palopo, 2026)
This study aims to optimize the employee performance management system of Atour Hotel Group, a medium-sized hotel chain in China, in order to better align employee behavior with organizational strategy and enhance sustainable competitiveness in the knowledge-based service economy. Many medium-sized service enterprises still rely on traditional appraisal systems characterized by limited indicators, rigid cycles, weak feedback, and low employee participation, which undermine motivation and restrict performance improvement. These challenges are particularly significant in the hotel industry, where service quality depends heavily on employee initiative and collaboration. Using a qualitative case study design, this research employs literature review, in-depth interviews, participant observation, and document analysis to evaluate the effectiveness of Atour’s existing system. The findings indicate weak strategic alignment, overly simplified performance indicators, insufficient continuous feedback, and poor integration between appraisal results and incentives, training, and career development. As a result, employee performance tends to be compliance-driven, service innovation is limited, and high-performing employees show relatively high turnover. Drawing on performance management theory, goal-setting theory, and self-determination theory, the study proposes a practical and theory-based performance management framework tailored to medium-sized service organizations. The proposed system emphasizes participatory SMART goal setting, multidimensional indicators based on the Balanced Scorecard, regular performance communication, transparent evaluation procedures, and differentiated reward and development mechanisms. A participatory, fair, and development-oriented system can enhance employee motivation, engagement, and service quality, thereby reducing turnover and supporting the achievement of organizational strategic objectives. These findings provide practical guidance for hotels and other service enterprises seeking to transform performance management into a strategic driver of employee development and organizational success.